2022
DOI: 10.7827/turkishstudies.64884
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of QR Menu Applications in Food and Beverage Businesses From Consumers' Perspective

Abstract: Teknolojide meydana gelen gelişmeler yiyecek içecek işletmelerinde klasik basılı menü kullanımı yerine günümüzde dijital menüleri popüler hale getirmektedir. QR menü, mobil cihazların kare kod okuma özelliğini kullanarak kullanıcıların menüye erişim sağlayabildiği güncel bir teknoloji türü olarak dikkat çekmektedir. Bu tür bir yeni teknolojiye dayalı menü kullanımı hakkında yiyecek içecek işletmesi tüketicilerinin sahip oldukları tutumların belirlenmesi, bu uygulamaların … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Literatür incelendiğinde (Cankül, 2019;Yim vd. 2020;Yılmaz, 2022) As customers become increasingly sensitive to the services offered in restaurants, smart restaurant applications that aim to transform the service offered in restaurants into a more efficient, facilitating, and user-friendly structure have played a decisive role in changing customers' preferences (Ghosh, Bhoir, Patel, Mehta and Mhatre, 2015). As technology has become more important recently, food and beverage business managers have started to use information communication technologies such as wireless internet and tablet menus to enrich their customers' dining experience (Gayke, Kaur, Gorhe, & Kore, 2017, p. 38).…”
Section: Sonuç Ve Tartışmamentioning
confidence: 99%
See 2 more Smart Citations
“…Literatür incelendiğinde (Cankül, 2019;Yim vd. 2020;Yılmaz, 2022) As customers become increasingly sensitive to the services offered in restaurants, smart restaurant applications that aim to transform the service offered in restaurants into a more efficient, facilitating, and user-friendly structure have played a decisive role in changing customers' preferences (Ghosh, Bhoir, Patel, Mehta and Mhatre, 2015). As technology has become more important recently, food and beverage business managers have started to use information communication technologies such as wireless internet and tablet menus to enrich their customers' dining experience (Gayke, Kaur, Gorhe, & Kore, 2017, p. 38).…”
Section: Sonuç Ve Tartışmamentioning
confidence: 99%
“…When the literature is examined (Cankül, 2019;Yim et al 2020;Yılmaz, 2022), it is seen that consumers are willing to use digital menus and find the use of digital menus interesting. As a result of the study, it was revealed that digital menu applications are in demand in restaurants.…”
Section: Sonuç Ve Tartışmamentioning
confidence: 99%
See 1 more Smart Citation